FULFILLMENT OF RIGHTS FOR COPYRIGHT HOLDERS AGAINST THE USE OF COPYRIGHTED WORKS OF SONGS FOR COMMERCIAL PURPOSES THROUGH REMIX COVER VERSIONS ON THE YOUTUBE PLATFORM - Febri Dwi Yanto; AL. Sentot Sudarwanto (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Moment YouTube is one of the primadonna platforms Because most applications are downloaded by the public. However, quite a phenomenon often found exists violation of rights created in a way commercial in the form of Remix Cover Version. With thereby study This needs to be done to explain the arrangement of fulfillment rights for the holder’s right to create songs used for interest commercials and liability on violation usage right to create work songs used for interest commercials via a remix cover version on the YouTube platform. Results and Discussion study This conclusion related to the fulfillment right to create a song is arranged in Constitution Number 28 of 2014 concerning the Right Which one do you create utilization work song attached right in a way exclusive from holder right create and everyone has obliged request agreement to holder right create and also give results profit commercial the in the form of royalties to the creator. If no is done, then a violation of Right Create specifically right economy is an inevitability. Next, users of YouTube are taking advantage of work songs through the remix cover version for interest commercials without the agreement of Holder Right Create, then can ask for accountability in a way civil and criminal.